Operational Guidance Note on Conditionality-December 2009 Revisions. (Policy Papers; Policy Paper ;, 2010)
The 2000-02 comprehensive review of the Fund's conditionality culminated in the adoption of a set of conditionality guidelines by the Executive Board on September 25, 2002. The 2002 Conditionality Guidelines (the 'guidelines') replace the 1979 Conditionality Guidelines and the Interim Guidance Note on Streamlining Structural Conditionality of September 18, 2000. A review of experience with the guidelines, looking at how they have been implemented and at their impact, is conducted periodically; summary statistics on conditionality have been prepared annually since 2008.